Chlamydia trachomatis ompA variants in trachoma: what do they tell us? - Aura A Andreasen; Matthew J Burton; Martin J Holland; Spencer Polley; Nkoyo Faal; David C W Mabey; Robin L Bailey (PLoS Neglected Tropical Diseases)
Background Trachoma, caused by Chlamydia trachomatis (Ct), is the leading infectious cause of blindness. Sequence-based analysis of the multiple strains typically present in endemic communities may be informative for epidemiology, transmission, response to treatment, and understanding the host response. Methods Conjunctival and nasal samples from a Gambian community were evaluated before and 2 months after mass azithromycin treatment. Samples were tested for Ct by Amplicor, with infection load determined by quantitative PCR (qPCR). ompA sequences were determined and their diversity analysed using frequency-based tests of neutrality. Results Ninety-five of 1,319 (7.2%) individuals from 14 villages were infected with Ct at baseline. Two genovars (A and B) and 10 distinct ompA genotypes were detected. Two genovar A variants (A1 and A2) accounted for most infections. There was an excess of rare ompA mutations, not sustained in the population. Post-treatment, 76 (5.7%) individuals had Ct infection with only three ompA genotypes present. In 12 of 14 villages, infection had cleared, while in two it increased, probably due to mass migration. Infection qPCR loads associated with infection were significantly greater for A1 than for A2. Seven individuals had concurrent ocular and nasal infection, with divergent genotypes in five. Conclusions The number of strains was substantially reduced after mass treatment. One common strain was associated with higher infection loads. Discordant genotypes in concurrent infection may indicate distinct infections at ocular and nasal sites. Population genetic analysis suggests the fleeting appearance of rare multiple ompA variants represents purifying selection rather than escape variants from immune pressure. Genotyping systems accessing extra-ompA variation may be more informative.